Initiative for self-control of blood sugar-diabetes in pregnancy - Wali, Aisha Syed; Ishtiaq, Annum; Rahim, Anum (International Journal Of Community Medicine And Public Health, 2021)
Our aim was to empower underprivileged women to self-control their blood glucose during pregnancy so that optimum blood glucose values and its monitoring can be achieved as outpatient care. A dedicated clinic was established for women with diabetes in pregnancy (DIP), that was focused on diabetes education and training of women. It was conducted by a team of a nutritionist, a trained midwife and residents. The challenges of unaffordability and language barrier were addressed. DIP clinic helped us cut down the cost of inpatient care. Awareness about DIP and its consequences on the baby motivated women to comply with medical nutrition therapy (MNT) and self-monitoring of blood glucose (SMBG). The women attained ownership and the feeling of fulfilment by taking charge of their blood glucose control for the benefit of their babies. This was a practical, cost-effective and successful health practice initiative of attaining glycemic targets in a lower middle-income population.